AB0658 Predictors of access to care in JSLE - evidence from the UK JSLE cohort study. (23rd January 2014) - Smith, E.; Taylor-Robinson, D.; Gray, W.; Foster, H.E.; Beresford, M.W.
Abstract : Background: Delays in access to specialist care for children with paediatric rheumatic disease are likely to be associated with adverse outcomes 1, 2 . Factors influencing access to care for Juvenile-onset Systemic Lupus Erythematosus (JSLE) remain mainly unknown. Objectives: We aimed to investigate factors that may influence the interval between symptom-onset and JSLE diagnosis within a UK cohort. Methods: Data from 257 patients recruited to the UK JSLE Cohort Study 3 were analysed. Potential predictors of access to care explored included: socioeconomic status, ethnicity, gender, age at presentation, presenting features, American College of Rheumatology (ACR) criteria, origin of referral to paediatric rheumatology, distance from nearest tertiary paediatric rheumatology service and family history of autoimmune disease. Correlation tests were employed to identify variables associated with a log of time between symptom-onset and diagnosis (p<0.1). Linear regression was then used to identify independent predictors of access to care. Results: 257 children from across the UK with JSLE were included in the analysis (216 females, 41 males, ratio 5.3:1). Median time from symptom-onset to diagnosis was 0.37 years (range 0-14.07 years, inter-quartile range [IQR] 0.17-1.38). Median distance to a tertiary paediatric rheumatology centre was 20.5 miles (IQR 9.2-41.5). The JSLE cohort population Index of Multiple Deprivation scores were found to be higher than the English population as a whole and not significantly associated with time to diagnosis (p=0.12). Variables correlating with time to diagnosis included: being British (correlation co-efficient +0.268, p=0.007), Caribbean or African (-0.159, p=0.011), presenting to a specific tertiary referral centre (0.139, p=0.026), being referred by a paediatrician (-0.130, p=0.037) and having nephritis (-0.138, p=0.027), immunological disorder (-0.125, p=0.046) or haematological disorder (-0.164, p=0.09) at presentation. A linear regression model identified being of Caribbean/African (p=0.006), Asian (p=0.045) ethnicity, referred by a paediatrician (p=0.047) or having nephritis (p=0.045) at presentation as independent predictors of shorter time to diagnosis. Conclusions: Within this cohort, ethnic origin and the initial source of referral were strong predictors of interval in establishing diagnosis of JSLE. Lupus nephritis at presentation is a significant independent predictor of shorter time to diagnosis. Gender, age at presentation, ACR score, distance from nearest tertiary paediatric rheumatology service, socioeconomic status and family history of autoimmune disease were not found to be significant predictors of access to care. References: Foster H et al. Access to Pediatric Rheumatology Care – A Major Challenge to Improving Outcome in Juvenile Idiopathic Arthritis. J Rheumatol 2010;37(11):2199-202. Hiraki LT et al. End-stage renal disease due to lupus nephritis among children in the US, 1995-2006. Arthritis Rheum 2011;63(7):1988-97. Watson L et al. Juvenile-onset SLE; disease activity, severity and damage – The UK JSLE Cohort Study. Arthritis Rheum, In Press, Dec 2011. Disclosure of Interest: None Declared